Estimation of genetic parameters for growth traits in Brahman crossbred cattle of Bangladesh (Journal of the Bangladesh Agricultural University, 2020)
The present study was conducted to estimate the genetic parameters (heritability and genetic correlation) and breeding value of Brahman crossbred cattle (50%) of Bangladesh. Data on 5662Brahman graded calves (50%) were collected from the records maintained by Department of Livestock Services from the eight areas of the country. Basic statistical analyses were performed by using Statistical Analysis System (SAS) version 9.1.3. Heritability and genetic correlations were estimated with Variance Component Estimation (VCE) 5.1.2 software and finally breeding values were measured with PEST software. Heritability (h2) estimates were 0.87, 0.59, 0.33, 0.33, 0.34, 0.34, 0.35 for birth weight (BW), Weight at 1-, 3-, 6-, 9-, 12- and 24-month (kg), respectively. Estimates of h2 for ADG from BW to 3-month (g), ADG from 3- to 6-month (g), ADG from 6- to 9-month (g), and ADG from 9- to 12-month (g) were found to be 0.53, 0.71, 0.69 and 0.68, respectively. Genetic correlations between growth traits ranged from 0.15 to 0.92 and phenotypic correlations between these traits ranged from 0.17 to 0.88. Average daily gain showed positive phenotypic correlation with all of the growth traits considered whereas genetic correlation ranged from -0.10 to 0.72. On the basis of predicted breeding value sire ID 60003 had the highest breeding value for body weight at different ages and average daily gain at different ages. Strong genetic and phenotypic correlations will help to improve growth traits simultaneously and selection at early stage can be effective for the improvement of growth traits at later ages.J Bangladesh Agril Univ 18(2): 421–427, 2020https://doi.org/10.5455/JBAU.98865